2021
DOI: 10.1111/adb.13096
|View full text |Cite
|
Sign up to set email alerts
|

Increased network centrality of the anterior insula in early abstinence from alcohol

Abstract: Abnormal resting‐state functional connectivity, as measured by functional magnetic resonance imaging (MRI), has been reported in alcohol use disorders (AUD), but findings are so far inconsistent. Here, we exploited recent developments in graph‐theoretical analyses, enabling improved resolution and fine‐grained representation of brain networks, to investigate functional connectivity in 35 recently detoxified alcohol dependent patients versus 34 healthy controls. Specifically, we focused on the modular organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 69 publications
(203 reference statements)
6
9
0
Order By: Relevance
“…In line with previous findings, AUD patients exhibited impairments in the insula and precuneus regions (Fukushima et al, 2020 ; Bordier et al, 2021 ). Recent fMRI studies have demonstrated that AUD can enhance activation in the insula, inferior frontal gyrus, and precuneus (Noori et al, 2016 ; Quaglieri et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with previous findings, AUD patients exhibited impairments in the insula and precuneus regions (Fukushima et al, 2020 ; Bordier et al, 2021 ). Recent fMRI studies have demonstrated that AUD can enhance activation in the insula, inferior frontal gyrus, and precuneus (Noori et al, 2016 ; Quaglieri et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, our study indicated that in AUD patients, functional alterations in the precuneus might affect the episodic memory-related circuits. A study has shown that insula as part of the salience network mediates external stimuli-induced attention and arousal responses (Bordier et al, 2021 ). The insula, as the central hub of the salience network, regulates attention shifting between the exogenous and endogenous states.…”
Section: Discussionmentioning
confidence: 99%
“…These studies will benefit from adopting a network perspective by applying systems level approaches and largely unbiased analyses strategies, as recently demonstrated in a large translational AUD research project ( Sommer et al, 2022 ) and the brain-wide investigation of cFos expression in 123 regions from chronically alcohol-drinking mice using light sheet microscopy that elegantly demonstrated decreased modularity of brain networks ( Kimbrough et al, 2020 ). These results are in line with our findings ( Wandres et al, 2021 ) and supported by recent fMRI results from animals ( Degiorgis et al, 2022 ; Pérez-Ramírez et al, 2022 ) and humans ( Bordier et al, 2022 ; Camchong et al, 2022 ), Targeting network modules, rather than individual brain regions non-invasively, holds therapeutic potential as demonstrated by a clinical trial in AUD patients using transcranial magnetic stimulation of the mPFC ( Harel et al, 2022 ).…”
Section: Conclusion Limitations and Future Directionssupporting
confidence: 92%
“…Similar alterations in global network organization have been shown for patients with AD independent of relapse status, 17–19 although results were not consistent across studies 20 . The present study extends previous work by highlighting deviations in network topology particularly in future relapsers.…”
Section: Discussionsupporting
confidence: 56%